2012
DOI: 10.1002/eji.201142093
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic tumor cells induce IL‐27 release from human DCs to activate Treg cells that express CD69 and attenuate cytotoxicity

Abstract: Summary Intrinsic immunosuppression is a major obstacle for a successful cancer therapy. Mechanisms how immunosuppression is induced and regulated in humans are ill-defined. A micro-environmental component that might prevent anti-tumor immunity is the presence of dying tumor cells, which is abundant following conventional cancer ablation methods such as chemo- or radiotherapy. Shedding of apoptotic debris and/or secretion of factors to the tumor bed or draining lymph nodes thus might have a profound impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 59 publications
1
41
1
Order By: Relevance
“…Previous studies have reported that IL-27 receptor knock-out down-modulates the expression of CD39 on dendritic cells and regulatory T cells. 52,53 LPS-stimulated human monocytes produce IL-27 ( Fig. S5A) and LPSstimulated macrophages expressed the transcript encoding IL-27, IL-27RA and gp130 (data not shown).…”
Section: The Expression Of Cd39 Is Regulated By Interleukin-27mentioning
confidence: 94%
“…Previous studies have reported that IL-27 receptor knock-out down-modulates the expression of CD39 on dendritic cells and regulatory T cells. 52,53 LPS-stimulated human monocytes produce IL-27 ( Fig. S5A) and LPSstimulated macrophages expressed the transcript encoding IL-27, IL-27RA and gp130 (data not shown).…”
Section: The Expression Of Cd39 Is Regulated By Interleukin-27mentioning
confidence: 94%
“…Sekar et al 18 have shown that apoptotic tumor cells prevent dendritic cells from establishing cytotoxicity toward living human tumor cells by inducing IL-27, thus stimulating a Treg cell population. This is the possible mechanism by which cancer patients in general may have increased levels of IL-27.…”
Section: Discussionmentioning
confidence: 99%
“…IL-27 induces CD39 + CD69 + Treg that inhibit anti-tumor CD73 + cytotoxic T cells to produce adenosine, that inhibit the effector T cells [183] and NK cells through adenosine receptor 2A [184]. IL-27 knockout mice have less Treg probably due to reduced IL-2 production [185].…”
Section: Role Of Il-27 In Induction Of Antigen Specific Tregmentioning
confidence: 99%